Improving Students' Reading Comprehension on Narrative Text Through Story Mapping Technique - Ajeng Anggita Pimpi; Endang Komariah; Dian Shafwati (English Language Education Study Program, 2026)
The objectives of this research were to find out whether any significant improvement of students’ reading comprehension after being taught through story mapping technique and which aspect of reading that improve the most after being taught through story mapping technique. This research was quantitative reasearch which used one-group pre-test and post-test design. The population of this research was the eleventh grade students of SMA Negeri 1 Seputih Banyak. The sample of this research was XI 2 which consisted of 35 students. The instruments for collecting the data was reading test which consisted of pre-test and post-test. The results were analyzed by using Paired Sample T-Test. The result of this research showed that the average score of the post-test (76.557) was higher than the pre-test (63.446). It increased by 13.1114. According to the results of the paired sample test, it was found that the t-value (13.162) is higher than the t-table (2.032). The significant value is less than 5% (0.00 < 0.05). The aspect of reading that improved the most after being taught through story mapping technique was inference. In this research, it was found that inference was the aspect that improved the most with an increase of 3.24. It can be concluded that story mapping technique can significantly improve students’ reading comprehension in narrative text.